E-Government: Online Company Domicile Certificate Service (SKDP) in East Jakarta - Robby, Uchaimid Biridlo’i; Warsono, Hardi; Dwimawanti, Ida Hayu; Triyuniningsih, Triyuniningsih (Interdisciplinary Social Studies, 2022)
The implementation of electronic-based government (Online), in order to improve the quality of effective and efficient public services through e-Government which aims to support good governance. The purpose of this study is to determine the implementation of e-Government implementation through the creation of an online Company Domicile Certificate (SKDP) at UP PTSP Lubang Buaya Village. In addition, this study is intended to find out various obstacles or obstacles and the efforts made by UP PTSP Lubang Buaya Village in overcoming these obstacles or obstacles. In this study, the researcher used George Edward III's theory of Policy Implementation which consists of 4 variables, namely communication, resources, dispotition or attitude, and bureaucratic structure with qualitative methods. Data collection techniques carried out in the form of observation, interviews and documentation. Data analysis using formulas from Miles and Huberman consists of data collection, data reduction, data presentation, and conclusion drawing. From the results of the study, the implementation of the application of e-Government in making a Company Domicile Certificate (SKDP) has not gone well. Obstacles found include lack of socialization, the ability of public servant officers, lack of public knowledge level and frequent site errors, as well as efforts made to overcome these obstacles, namely by more frequent socialization about online licensing, training for employees, and coordination with the center regarding sites that often error. So that people can feel good and satisfying service and switch to an online-based service system.